Poetisk viden? Bruno Latours favntag med æstetikken - Schmidt, Johanne Gormsen (K&K - Kultur og Klasse, 2020)
This article examines the current efforts to rethink the perception of facts and fiction and the relation between the two arising in both academia and literature. Bruno Latour’s repudiation of the modern division of subject and object implies that the hard facts of traditional science cannot be sharply dissociated from art and soft values. In tandem with Latour’s increasing influence in a number of academic disciplines, a strong engagement with factual matters has appeared in literature. The field of science and the field of aesthetics thus seem to approach each other from both sides, science leaning towards artistic practices and fiction leaning towards facts. In his search for an alternative knowledge acquisition, Latour turns to aesthetic devices. Following this lead, the aesthetic attention of Pejk Malinovski and the recently actualized Frank O’Hara and Robert Walser appears to insist on meeting things openly, in their specific situations and concrete exchanges, inspiring Latour’s call for a transformation of matters of fact into matters of concern. The question is, however, to what extent Latour’s perspective is able to make real scientific use of this kind of production of meaning. Considering Martin Heidegger’s and Hannah Arendt’s views on the relation of technology, knowledge, value, and art, it seems that Latour after all might not be that disengaged from modern philosophy and the modern stress on separation rather than mediation.